Management of pregnant women with a previous cesarean section. - Yui, Lorena (2015)
Retrospective study of 1045 pregnant women with one previous cesarean section attended at the Maternal Perinatal Intitute from january 1 through December 3l, 1992. Patients were divided in two groups according to achievement of vaginal delivery or repeat cesarean section, vaginal delivery was obtained in 80% of 561 patients allowed labor. Instrument delivery occured in two patients. Repeat cesarean section was performed either because of absolute obstetrical indication in 475patients (76,7>%) or due to the obstetrician´s criteria in 121 patients (20,3%). Main indication of cesarean section inpatients who jailed trial of labor was fetal distress (44%). Uterine wound dehiscence was found in 1,53%. Placental complications included placenta accreta and placenta previa in 0,29% and 1,44 respectively. There were no maternal deaths. More puerperal morbidity and more days of hospitalization were statistically found in patients submitted to new cesarean section. Newborn morbidity and mortality was similar in the two groups.